On a class of nonuniformly nonlinear systems with Dirichlet boundary conditions - Afrouzi, G.A.; Naghizadeh, Z.; Chung, N.T. (Український математичний журнал, 2014)
The existence and multiplicity of weak solutions for some nonuniformly nonlinear elliptic systems are obtained by using the minimum principle and the Mountain-pass theorem. Існування та кратність слабких розв'язків деяких нерівномірно нєлінійних еліптичних систем досліджено за допомогою принципу мінімуму та теореми про гірський перевал.